Variable modes of inheritance of morphometrical traits in hybrids between Drosophila melanogaster and Drosophila simulans. - David, J R (2002)
We investigated body-size inheritance in interspecific sterile hybrids by crossing a Drosophila simulans strain with 13 strains of Drosophila melanogaster, which were of various origins and chosen for their broad range of genetic variation. A highly significant parent-offspring correlation was observed, showing that the D. melanogaster genes for size are still expressed in a hybrid background. Superimposed on to this additive inheritance, the size of hybrids was always less than the mid-parent value. This phenomenon, which at first sight might be described as dominance or overdominance, is more precisely interpreted as a consequence of a hybrid breakdown, that is, a dysfunction of the parental genes for size when put to work together. This interpretation is enforced by the fact that phenotypic variability was much more prevalent in hybrids than in parents. We also analysed body pigmentation inheritance in the same crosses and got a very different picture. There was no increase in the phenotypic variance of F(1) hybrids and only a low parent-offspring correlation. Apparent overdominance could be observed but in opposite directions, with no evidence of hybrid breakdown. Our data point to the possibility of analysing a diversity of quantitative traits in interspecific hybrids, and indicate that breakdown might be restricted to some traits only.